The relationship between health literacy and self-care management in patients with hypertension attending primary healthcare centers. - Esen, Kübra; Kolcu, Merve (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: In hypertension management and therapy adherence, the level of health literacy is a significant factor likely to contribute to improved self-care management by patients. This research was conducted to identify the relationship between health literacy and self-care management in patients diagnosed with hypertension. Subject and methods: A total of 210 patients with hypertension who presented to the family practice polyclinic of a training and research hospital and the family health center affiliated with this hospital were included in this descriptive study. The research data were collected with the patient identification form, the Self-Care Management Processes-Guarding Scale, and the Health Literacy Scale. Results: The mean age of patients was 53.80±8.41 years, and 70% were female. Statistically significant differences were identified in patients' mean Self-Care Management Processes-Guarding Scale scores according to age, employment status, and status of cigarette smoking; in addition, statistically significant differences were found in patients' mean Health Literacy Scale scores based on age, marital status, education level, employment status, economic status, attention to diet, and regular engagement in physical exercise. Moreover, a positive correlation was identified between patients' Self-Care Management Processes-Guarding Scale and Health Literacy Scale scores (P <.05). Conclusion: Efforts should be made to identify hypertensive patients' self-care management and health literacy levels. It is recommended that hypertension training course material be prepared based on patients' health literacy levels to offer in the context of primary healthcare services to develop self-care management.